Effect of Mulch on the Growth and Yield of Polianthes tuberosa - Sihombing, Donald; Handayati, Wahyu (KnE Life Sciences, 2017)
Tuberose is one of the most important ornamental plants in Indonesia which the demand continuously increases. However, tuberose is commonly cultivated in drained rice fields and this resulted in various problem such us weed and insect infestation especially mealybug in dry season. In this regard a study was conducted in Malang Regency at Karangploso Experimental Station of East Java Assessment Institute for Agriculture Technology from March 2012 to April 2013. The study employed an experimental method using a randomized block design. Two varieties of tuberoses, i.e., Dian Arum (double flowering) and Roro Anteng (semi-double flowering) were planted on a prepared soil bed. Both tuberose varieties were treated by a silvery plastic mulch cover on one bed and none on the other. Results showed significant differences between the mulch and without mulch treatments in terms of plant growth and flower production. Flower production obtained from mulch treatment was 3.8 stalks/clump or 34.22 stalks/m2, whereas that without mulch was 2.47 stalks/clump or 27.44 stalks/m2. Meanwhile the damage intensity caused by mealybug infestation on the mulch treatment was 15.21%, while that without mulch was 22.17%. In fact, the use of mulch could reduce the weeding cost up to 66.67 % and the total production cost up to 20.86%. The result obtained from R/C ratio analysis with mulch treatment was 2.59 whereas that without mulch was 1.71. Keywords: Polianthes tuberosa ; mulch; weed, pest; yield; R/C ratio